Dealing with Loneliness: A Psychoanalysis Reading of “Smoking with God, The Dollhouese, The Sandcastle” by Rain Chudori (2015) - Firanisa Atzama; Delvi Wahyuni (English Language and Literature, 2022)
This research is an analysis of the story by Rain Chudori entitled Smoking with God, The Dollhouse and The Sandcastle (2015). This analysis explores how the character deals with loneliness in each story. The study of this novel is analysed with the psychoanalysis theory and supported by human psyche and defence mechanism. The results of this study show that part of the psychoanalysis of the human psyche and defence mechanism that occurs in the character. This research will include; 1) human psyche and 2) defence mechanism.